Ação antimicrobiana de óleos essenciais de Thymus vulgaris L. e Satureja hortensis L. e seus componentes contra Salmonella spp. na forma planctônica e em biofilme - Amaral, Viviane Cristina de Souza (2014)
Adesion and biofilm formation on polypropylene surfaces can be source of cross-contamination in food processing plants, leading major threat to public health and food quality. Several strategies to control bacterial adhesion to surfaces have been proposed, including the use of natural compounds. In this study Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of Thymus vulgaris L. (Thyme) and Satureja hortensis L. (Savory) essential oils (EOs) and its predominant compounds against Salmonella spp. was evaluated and the combination of the active compounds of carvacrol and thymol . It was also evaluated the effect of carvacrol and thymol against Salmonella spp. biofilms on polypropylene. The EOs were obtained by hydrodistillation apparatus and the chemical composition was analyzed by mass spectrometry gas chromatography and nuclear magnetic resonance. MIC and MBC were determined using a broth microdilution method and the synergistic effect was assessed by the checkerboard method. The effect of carvacrol and thymol on Salmonella spp. biofilms on polypropylene was evaluated using different concentrations of the compounds by Colony Forming Units (CFU) counting assay and by scanning electron microscopy. It was observed that essential oils and their compounds showed anti-Salmonella spp. activity and the combination of the compounds showed synergism (0,141 FIC). Carvacrol and thymol also reduced the number of bacterial cells on polypropylene the surface at all concentrations tested. Peracetic acid, a standard sanitizer, was used as control, showed MIC and MBC of 100 ppm and drastically reduced bacterial counts on polypropylene. We conclude that carvacrol and thymol were effective against Salmonella spp. established biofilms and during its formation on polypropylene; however the effectiveness of control sanitizing was superior. Thus, natural compounds tested appear to be an alternative to control Salmonella biofilms on surfaces with low contamination.